Preparation and Characterization of Ni–TiO2 Nanocomposite Coatings Produced by Electrodeposition Technique - Birlik, Isil; Ak Azem, N. Funda; Toparli, Mustafa; Celik, Erdal; Koc Delice, Tulay; Yildirim, Sidika; Bardakcioglu, Onur; Dikici, Tuncay (Frontiers in Materials, 2016)
In this paper Ni-TiO2 nanocomposite coatings with different sizes of TiO2 nanoparticles were successfully prepared by electrodeposition process from a nickel electrolyte in which the TiO2 nanoparticles were suspended. The influence of relevant deposition parameters on the nanocomposite coating characteristics was discussed. X-ray diffractometer (XRD) has been applied in order to investigate the phase structure of the nanocomposite coatings. The surface morphology of nanocomposite coatings was characterized by a scanning electron microscopy equipped with an energy dispersive spectroscopy (SEM/EDS). The electrodeposited nanocomposite coatings obtained at different deposition parameters were evaluated for their mechanical and corrosive properties. Obtained results show that the size of TiO2 nanoparticles and applied current density during deposition process has a direct effect on mechanical and corrosive properties of nanocomposite coatings. Increasing current density and smaller nanoparticle size has affirmative effect on mechanical properties whereas corrosion resistance of nanocomposite coatings deposited at 3 A.dm-2 current density are higher than the coatings prepared at higher current density values.